Multi-domain Software Defined Networking: Research status and challenges. (1st June 2017) - Wibowo, Franciscus X.A.; Gregory, Mark A.; Ahmed, Khandakar; Gomez, Karina M.
Abstract: A key focus of the transition to next generation computer networking is to improve management of network services thereby enhancing traffic control and flows while simplifying higher-level functionality. Software-defined networking (SDN) is an approach that is being developed to facilitate next generation computer networking by decoupling the traffic control system from the underlying traffic transmission system. SDN offers programmability in network services by separating the control plane from the data plane within network devices and providing programmability for network services. Enhanced connectivity services across the global digital network require a multi-domain capability. This paper presents a review of the current research status in SDN and multi-domain SDN, focusing on OpenFlow protocol, and its future related challenges.